Severe hemolysis and vaso‐occlusive crisis due to COVID‐19 infection in a sickle cell disease patient improved after red blood cell exchange - Lina Okar (14777164) (2023)
Even though most data suggest favorable outcome in patients with SCD and COVID-19 infection, close monitoring remains essential as acute complication may develop unexpectedly. Offering RBC exchange early in the course of infection might improve prognosis. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.3960